AKUMULASI CUT-OFF PADA UKM MEBEL - Prahasto, Toni (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
This article presents the generation and accumulation of cut-off waste in furniture small enterprises. The sequence of processes in observation is aimed at producing a simple wooden component, and consists of five machining processes. The dimension of the component has a bounding box of 3 cm by 17 cm by 81 cm. The average productivity of the machines is 120 pieces per shift. The rate of defected product and waste vary from one to other machines, all of which have less than 10% of waste. However, the observation reveals that the accumulation of defect almost reaches 30%; this by product has potential to be recycled to produce components with bounding boxes smaller than that mentioned above.